2018
DOI: 10.1093/toxsci/kfy204
|View full text |Cite
|
Sign up to set email alerts
|

Fatty-Acid Binding Protein 4 (FABP4) as a Potential Preclinical Biomarker of Drug-Induced Kidney Injury

Abstract: Identification of improved translatable biomarkers of nephrotoxicity is an unmet safety biomarker need. Fatty-acid-binding protein 4 (FABP4) was previously found to be associated with clinical renal dysfunction and was proposed as a biomarker of glomerular damage. The aim of this study was to evaluate FABP4 as a potential preclinical biomarker of drug-induced kidney injury (DIKI). Han-Wistar rats were dosed with cisplatin [2.5 mg/kg, single, intraperitoneally (i.p.)], puromycin (10 mg/kg, daily, i.p.) or N-phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Our study is probably the first to report the urine FABP4 levels in the early puerperal mothers, yet we did not find any significant differences in this parameter between the healthy, EGWG, and GDM women. Urine, as a material for the assessment of FABP4 concentrations in the human studies, has been used in patients with glomerular injury, as well as with acute and chronic renal dysfunction [23,24,25]. Due to its small molecular size, this protein may escape the glomerular sieves and be excreted in the urine if not reabsorbed by the renal tubules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study is probably the first to report the urine FABP4 levels in the early puerperal mothers, yet we did not find any significant differences in this parameter between the healthy, EGWG, and GDM women. Urine, as a material for the assessment of FABP4 concentrations in the human studies, has been used in patients with glomerular injury, as well as with acute and chronic renal dysfunction [23,24,25]. Due to its small molecular size, this protein may escape the glomerular sieves and be excreted in the urine if not reabsorbed by the renal tubules.…”
Section: Discussionmentioning
confidence: 99%
“…However, the evaluation of FABP4 in the early post-partum period has not been performed so far. Furthermore, available studies on the urine FABP4 concentrations are limited to the patients with acute and chronic renal dysfunction [23,24,25]. As far as we know, the FABP4 levels in the urine of both GDM patients and EGWG women have not been investigated before.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating FABP4 has been reported to be processed by the kidney and reabsorbed through megalin, an endocytic receptor expressed in proximal tubule epithelial cells [ 34 ]. It has also been shown that U-FABP4 is increased before an increase in serum creatinine, clusterin or cystatin C in a drug-induced glomerulonephritis model with N-phenylanthranilic acid and puromycin in in vivo and in vitro studies [ 35 ]. Newly expressed and secreted FABP4 in the glomerulus may pass through glomerular filtration barriers, and an excess of FABP4, which exceeds the permissible amount of reabsorption in proximal tubular cells, is excreted into urine, resulting in reflection of the extent of glomerular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we analysed three rat models of DIKI using phosphoprotein microarrays. Cisplatin, puromycin and NPAA were selected based on their ability to induce proximal tubule, glomerular and collecting duct injury respectively . This allowed us to identify phosphoprotein signatures associated with region‐specific kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…This might be a consequence of a recovery from injury after a single administration of cisplatin confirmed by the lack of histopathological lesions in proximal tubules on day 28. 5 Contrary to cisplatin, daily administration of puromycin resulted in the number of dysregulated phosphoproteins increasing over time.…”
mentioning
confidence: 99%